2009
DOI: 10.1371/journal.pone.0005651
|View full text |Cite
|
Sign up to set email alerts
|

A New Family of Receptor Tyrosine Kinases with a Venus Flytrap Binding Domain in Insects and Other Invertebrates Activated by Aminoacids

Abstract: BackgroundTyrosine kinase receptors (RTKs) comprise a large family of membrane receptors that regulate various cellular processes in cell biology of diverse organisms. We previously described an atypical RTK in the platyhelminth parasite Schistosoma mansoni, composed of an extracellular Venus flytrap module (VFT) linked through a single transmembrane domain to an intracellular tyrosine kinase domain similar to that of the insulin receptor.Methods and FindingsHere we show that this receptor is a member of a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(111 citation statements)
references
References 50 publications
9
102
0
Order By: Relevance
“…cRNA was also produced from a pcDNA 3.1 plasmid encoding full-length SmVKR1 (23) rendered constitutively active by an exchange of the Phe-1167 (close to the potential YY1064 -1065 autophosphorylation site) to a glutamic acid residue (SmVKR1 YYRE ) performed by site-directed mutagenesis as described before (24,25). SmVKR1 YYRE -C-term was amplified by PCR from SmVKR1 YYRE in pcDNA 3.1 using the primer pair SmVKR1-C-term-5Ј (5Ј-CCCTGCAGTCAAGGTAGAA-ACGCTAAACTGTTATC-3Ј; containing a PstI site) and SmVKR1-C-term-3Ј (5Ј-GGGAATTCCGACGTAAACTGA-AAGAAATTGAAAATCG-3Ј; containing an EcoRI site) and subcloned in the T7-containing plasmid PGBKT7 that also contains the Myc tag.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…cRNA was also produced from a pcDNA 3.1 plasmid encoding full-length SmVKR1 (23) rendered constitutively active by an exchange of the Phe-1167 (close to the potential YY1064 -1065 autophosphorylation site) to a glutamic acid residue (SmVKR1 YYRE ) performed by site-directed mutagenesis as described before (24,25). SmVKR1 YYRE -C-term was amplified by PCR from SmVKR1 YYRE in pcDNA 3.1 using the primer pair SmVKR1-C-term-5Ј (5Ј-CCCTGCAGTCAAGGTAGAA-ACGCTAAACTGTTATC-3Ј; containing a PstI site) and SmVKR1-C-term-3Ј (5Ј-GGGAATTCCGACGTAAACTGA-AAGAAATTGAAAATCG-3Ј; containing an EcoRI site) and subcloned in the T7-containing plasmid PGBKT7 that also contains the Myc tag.…”
Section: Methodsmentioning
confidence: 99%
“…SmVKR1 (previously called SmRTK-1) was described as an unusual schistosome RTK composed of an extracellular Venus Flytrap module (a ligand-binding domain in class 3 G-proteincoupled receptors) linked by a single transmembrane domain to a TK domain, which displayed similarity to that of insulin receptors (23). Venus kinase receptors have been found in different invertebrates, particularly in insects (24). As in schistosomes, Venus kinase receptors are mainly expressed in female gonads, indicating a putative function of these receptors in reproduction and/or development.…”
Section: Transcriptional Analyses Demonstrate Similar Activity Profilmentioning
confidence: 99%
“…1B). It also contained 10 predicted N-glycosylation sites plus a Venus flytrap (VFT) module known from several proteins including a subset of RTKs in insects and other invertebrates (23,24). Quantitative real-time PCR (qRT-PCR) indicated that AAEL001915 expression was higher in the ovaries of 5-d-old nonblood female A. aegypti than in the fat body and midgut (Fig.…”
Section: Significancementioning
confidence: 99%
“…VFT modules are known from several types of membrane proteins including bacterial periplastic proteins and select GPCRs and RGCs (23). In contrast, VFT modules are unknown in PRKs, with the exception of a subset of RTKs in arthropods and select other invertebrate phyla recently named the Venus Kinase Receptor family (23,30). All genes in the OR1 clade of our dipteran phylogeny are members of this assemblage.…”
Section: Oeh Binds To Aael001915 and Activates Phosphosphorylation Ofmentioning
confidence: 99%
See 1 more Smart Citation